RELATIONSHIP BETWEEN MATHEMATICAL PROBLEM SOLVING ABILITY & MATHEMATICAL COMMUNICATION ABILITY OF GRADE VII STUDENTS AT SMP NEGERI 2 ACADEMIC YEAR 2022/2023 - Laia, Serupa; Surven (Universitas Nias Raya, 2022)
This research is motivated by the ineffectiveness of students' mathematical problem-solving abilities and mathematical communication abilities. This study aims: to determine whether there is a relationship between students' mathematical problem-solving skills and students' mathematical communication skills. The type of research used is quantitative research with correlational methods. The population in this study was class VII with a total of 67 students. Sampling was carried out using total sampling technique, which means that all populations were used as samples. The research instrument used was a test of the ability to solve mathematical problems and mathematical communication skills. Data analysis used the prerequisite test of the linear regression model, the correlation coefficient test of the Product Moment formula, the correlation coefficient t test, and the coefficient of determination.